Deep insemination with sex‐sorted Cashmere goat sperm processed in the presence of antioxidants. (3rd December 2017) - Qin, Y; Yang, S; Xu, J; Xia, C; Li, X; An, L; Tian, J
Contents: Flow cytometrically sex‐sorted sperm have been widely used for improving reproductive management in the dairy industry. However, the industrial application of this technology in other domestic species is largely limited by the lower fertility after insemination. The aim of this study was to investigate effects of antioxidant supplementation during the sex‐sorting and freezing process on the quality and functions of sorted sperm from Liaoning Cashmere goats. We tested the effects of antioxidant supplementation during sex‐sorting and freezing process, including ascorbic acid‐2‐glucoside AA‐2G, glutathione, melatonin and vitamin C (VC), on the quality and functions of sex‐sorted fresh and frozen‐thawed sperm. Based on these experiments, we performed deep insemination with sex‐sorted sperm using our improved strategy, in comparison to unsorted sperm. In Experiment 1, compared with control group and other antioxidants, AA‐2G supplementation significantly alleviated the degradation of motility and viability of fresh sperm after sorting and showed the highest percentage of sperm with normal morphology. In addition, AA‐2G supplementation showed an evident protection against the sorting process‐induced membrane and acrosome damage. In Experiment 2, AA‐2G supplementation was most effective in protecting motility, while melatonin supplementation appears to facilitate the degradation of quality of frozen‐thawed sex‐sorted sperm. In Experiment 3, we performed deep insemination with sperm that were sorted and frozen in the presence of AA‐2G and obtained a satisfying pregnancy rate comparable to that from unsorted sperm. The results showed that AA‐2G supplementation efficiently protects quality and function of both fresh and frozen‐thawed sex‐sorted sperm of Cashmere goats, thus obtaining a satisfying pregnancy outcome.